2009
DOI: 10.1097/mao.0b013e3181bc3c06
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Electrophysiologic Findings of Round Window Stimulation in a Model of Experimentally Induced Stapes Fixation

Abstract: Mechanical stimulation of the RW in an animal model of SF generates functionally similar inputs to the cochlea as normal acoustic and RW mechanical inputs but with increased thresholds. With further study, AMEIs may provide a surgical option for correction of otosclerosis and ossicular chain disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 53 publications
6
28
3
Order By: Relevance
“…These factors may include the shape of the transducer and the area of the RW it covers. Most significant is whether the transducer completely covers the RW, as demonstrated by other groups [27][28][29], or leaves an RW area partially free [26,[30][31][32]. The outcome of our experiments reveals that partial coverage of the RW may not affect RW impedance sufficiently to affect cochlear stimulation with the exposed portion of the RW membrane acting as a pressure shunt (figure 5).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…These factors may include the shape of the transducer and the area of the RW it covers. Most significant is whether the transducer completely covers the RW, as demonstrated by other groups [27][28][29], or leaves an RW area partially free [26,[30][31][32]. The outcome of our experiments reveals that partial coverage of the RW may not affect RW impedance sufficiently to affect cochlear stimulation with the exposed portion of the RW membrane acting as a pressure shunt (figure 5).…”
Section: Discussionmentioning
confidence: 62%
“…Furthermore, where we found RW stimulation through the partially occluded RW elicited stapes displacements only at high intensities below 7 kHz, under similar stimulus conditions, Lupo et al [30] observed stapes movement in chinchillas across a wider frequency range of 0.25-16 kHz. We suggest that tighter hydromechanical coupling between the RW transducer and the stapes, and consequent changes in the hydromechanical properties of the cochlea after stapes immobilization, may account for elevation of the CAP thresholds after stapes fixation observed by Lupo et al [30]. Correspondingly, differences in transducer shape and the proportion of the RW covered may potentially account for differences in the transducer-stapes hydromechanical coupling reported in this study and by Lupo et al [30].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…1,2 In-vivo stimulation at the RW has presented a similarly confounding picture. Recently, cochlear microphonics, compound action potential and auditory brainstem response were measured in chinchilla in response to both normal auditory stimulation and RW stimulation by means of a middle-ear transducer (MET) from Otologics, equipped with a 1-mm diameter ball tip without intervening material (Lupo et al, 2009). Again, estimating the ratio of stapes displacement relative to actuator displacement at the RW, we obtain a value of 0.001 (À60 dB).…”
Section: Introductionmentioning
confidence: 99%